Wordslut [book club bag] : a feminist guide to taking back the English language - Montell, Amanda (Harper Wave, an imprint of HarperCollinsPublishers, 2019)
A brash, enlightening, and wildly entertaining feminist look at gendered language and the way it shapes us, written with humor and playfulness that challenges words and phrases and how we use them. The word bitch conjures many images for many people, but it is most often meant to describe an unpleasant woman. Even before its usage to mean a female canine, bitch didn<U+2019>t refer to gender at all<U+2014>it originated as a gender-neutral word meaning genitalia. A perfectly innocuous word devolving into a female insult is the case for tons more terms, including hussy<U+2014>which simply meant housewife<U+2014>or slut, which meant an untidy person and was also used to describe men. These words are just a few among history<U+2019>s many English slurs hurled at women. Amanda Montell, reporter and feminist linguist, deconstructs language<U+2014>from insults and cursing, gossip, and catcalling to grammar and pronunciation patterns<U+2014>to reveal the ways it has been used for centuries to keep women and other marginalized genders from power. Ever wonder why so many people are annoyed when women talk with vocal fry or use the word like as a filler? Or why certain gender-neutral terms stick and others don<U+2019>t? Or where stereotypes of how women and men speak come from in the first place?